REVEALS reconstruction of past vegetation cover with original RPP values for South American samples - Herzschuh, Ulrike; Ewald, Peter; Schild, Laura; Li, Chenzhi; Böhmer, Thomas (PANGAEA, 2023)
This data set presents the reconstructed vegetation cover for 173 South American sites based on harmonized pollen data from the data set LegacyPollen 2.0 (https://doi.pangaea.de/10.1594/PANGAEA.929773). Sugita's REVEALS model (2000) was applied to all pollen records using REVEALSinR from the DISQOVER package (Theuerkauf et al. 2016). Pollen counts were translated into vegetation cover by accounting for taxon-specific pollen productivity and fall speed. Additionally, relevant source areas of pollen were calculated using the aforementioned taxon-specific parameters and a gaussian plume model for deposition and dispersal and forest cover was reconstructed. Values for relative pollen productivity and fall speed from the synthesis from Wiezcorek and Herzschuh (2010) were used for the reconstruction of vegetation cover. The average values from all Northern Hemisphere values were used where taxon-specific continental values were not available. We present tables with reconstructed vegetation cover for all continents with original parameters. As further details we list a table with the taxon-specific parameters used and a list of parameters adjusted in the default version of REVEALSinR.
Keywords: fossil pollen; paleoecology; REVEALS